Implementation of the Cooperative Learning Model to Improve Forearm Passing Ability in Volleyball Among Students at SMP N 2 Purwanegara - Septiyani, Valen Septiyani; Wahyudi , Agung (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This research aims to analyze the implementation of the Cooperative Learning Model in improving the mastery of forearm passing techniques in volleyball among eighth-grade students at SMP Negeri 2 Purwanegara. The main premise of the research is based on the need for physical education learning that not only emphasizes skill repetition but also involves interaction, cooperation, observation, peer feedback, and learning responsibility. The research uses an action research design implemented in two cycles through the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 32 eighth-grade students. Data were collected through attitude observations, knowledge tests, and forearm passing performance assessments. Data analysis included descriptive statistics, classical mastery percentage, percentage improvement, N-Gain, Shapiro–Wilk normality tests, and paired-samples t-test. The results showed that the mean knowledge score increased from 67.81 in Cycle I to 82.81 in Cycle II, while classical mastery increased from 31.25% to 84.38%. In the skill domain, the mean score increased from 56.45 to 86.52, representing a 53.29% improvement, accompanied by a positive shift in skill categories and the absence of students in the Poor category in Cycle II. The mean attitude score increased from 78.32 to 83.98, while the proportion of students in the Very Good category increased from 9.4% to 28.1%. Paired-samples t-tests showed significant differences between Cycle I and Cycle II in the knowledge, attitude, and skill domains (p < .000). N-Gain analysis indicated moderate improvement in knowledge (0.51) and high improvement in skills (0.71). Thus, the action hypothesis was accepted, indicating that the implementation of the Cooperative Learning Model was associated with meaningful improvements in volleyball forearm passing and supported positive development across cognitive, affective, and psychomotor learning outcomes. Keywords: cooperative learning, forearm passing, volleyball, learning outcomes, action research.